Understanding Rape Myth Acceptance: The Impact of Ambivalent Sexism and Conservatism in Surabaya - Wulandari, Adinda Dwi; Margaretha, Margaretha (Jurnal Psikologi, 2022)
This study aims to analyze the impact of ambivalent sexism and conservatism on rape myth acceptance. Using a quantitative survey approach, this study assessed rape myth acceptance in a sample from Surabaya to represent urban societies in Indonesia. Ambivalent sexism towards women is constructed with hostile sexism (women are cunning) and benevolent sexism (women are weak and should be protected), measured by the Extended Ambivalent Sexism Inventory(α = .88). The Conservatism Scale measured beliefs to maintain traditional values and oppose changes (α = .77). Rape myth acceptance was measured by a vignette scale developed by researchers with two scenarios: the victim is familiar or non-familiar to the perpetrator (α = .87). Data from 381 respondents aged 18-40 years were collected and analyzed using Pearson correlation, ANOVA, t-test, and hierarchical linear regression. Results show that rape myth acceptance familiar scenario is influenced by conservatism and hostile sexism(R2 = .11;F(4,380) = 12.49p< .001).Rape myth acceptance non-familiar scenario is also influenced by conservatism and hostile sexism(R2 = .15;F(4,380) = 17.14,p< .001). Individuals who hold hostile sexism attitude toward womenand rigidly maintain traditional values tend to believe in rape myths. This research encourages structured and sustainable social interventions to dismantle rape myth acceptance, conservatism, and sexism towards women in Indonesian society.